Economic Analysis of the Chemical Industry of the Czech Republic in the Period of Economic Growth - Vlček, David; Košťálová, Jana (UNIV HRADEC KRALOVE, 2020)
The chemical industry accounts for less than 1 % of the Czech Republic's industry, and this percentage has been decreasing due to the growth of other industries. Despite this, it has an important position, especially in terms of input producer for other areas of industry and agriculture. The percentage of employees and their wages in the chemical industry has been increasing recently. In the period of economic growth, the growth of the chemical industry has been recorded in all important indicators - value added, profit, sales and investment. Foreign trade in chemical products has a long-term negative balance in the Czech Republic. The article discusses the situation in the chemical industry of the Czech Republic over the last eight years from the economic point of view compared with the industry as a whole, the outputs of the financial analysis of the chemical industry compared with the manufacturing industry. There are also described the challenges and problems the chemical industry is currently facing. These include slowing economic growth, the emergence of new technologies known as Industry 4.0, the lack of workers in the labour market, the changing demands of workers and the increasing demands for accountability and sustainability of business activities.
Ekonomická analýza chemického průmyslu České republiky v období ekonomického růstu
Keywords: chemical industry; economic indicators; Czech Republic; chemický průmysl; ekonomické ukazatele; Česká republika